Epidemiological profile of the population assisted in an oral cancer tracking program: sociodemographic characteristics, life habits, and clinical conditions - Silveira Nunes, Maria; Guedes Ramos, Cybele; Veloso Suzart, Mariana; Furletti Nunes Barros Rego, Renata; Bernardina Miranda Soares, Príscila; Fagundes Silveira, Marise; Rodrigues de Melo Filho, Mario (Revista Unimontes Científica, 2020)
Perfil epidemiológico da população assistida em um programa de rastreamento de câncer de boca: características sociodemográficas, hábitos de vida e condições clínicas ABSTRACT: Objective: This work aims to describe the sociodemographic, behavioral and clinical profile of the population attended in the oral cancer prevention exams during the 8th Cancer Prevention Campaign that took place in the municipality of Montes Claros, MG, Brazil, in 2018. Methods: A descriptive study was carried out based on the data obtained in the attendances performed in the Dentistry Tent during the 8th Cancer Prevention Campaign using a structured questionnaire covering their sociodemographic data, cancer family history, and behavioral characteristics. In order to obtain the clinical data related to oral neoplasms, oral examinations were performed by dentists. Frequency tables and graphs were used for the descriptive tabulation. Results: Oral cancer prevention exams were performed in 396 individuals, with an average age of 56.5 years, and the majority of them being women (66.1%). Most of the participants reported a cancer family history (55.2%), were active smokers (60.6%), and were not alcohol consumers (60.4%). A total of 36.6% of the participants reported the practice of physical activities three times a week. Only 1.8% reported a previous history of neoplasm. The most prevalent clinical features included dysphagia (19.9%), non-healing wounds (15.0%), and dysphonia (14.4%). Conclusion: The Cancer Prevention Campaign is extremely important regarding oral cancer, since it allows the screening, early diagnosis, and a better prognosis of this disease. Resumo: Objetivo: Descrever o perfil sociodemográfico, comportamental e clínico da população assistida nos exames de prevenção de câncer de boca durante o 8º Mutirão de Prevenção ao Câncer no ano de 2018, realizado no município de Montes Claros, MG. Metodologia: Estudo descritivo que utilizou dados dos exames de prevenção de câncer de boca durante o 8º Mutirão de Prevenção ao Câncer. Foi adotado um questionário estruturado constituído por características sociodemográficas, histórico familiar de câncer e hábitos de vida. Para obtenção dos dados clínicos referentes à neoplasia de boca foram realizados exames bucais com odontologistas. Para descrição dos dados foram utilizados tabelas de frequência e gráficos. Resultados: foram realizados exames de prevenção do câncer de boca em 396 indivíduos com média de idade de 56,5 anos, cuja maioria era do sexo feminino (66,1%). Mais da metade dos participantes relataram história familiar de câncer, e prevaleceram pacientes que nunca fumaram (60,6%) e nunca beberam (60,4%). A prática de atividade física em três vezes na semana foi relatada por 36,6% dos participantes. 1,8% relataram história pregressa de neoplasia. Quanto às características clínicas mais prevalentes destaca-se a disfagia (19,9%), feridas que não cicatrizam (15,0%) e disfonia (14,4%). Conclusão: no que diz respeito ao câncer de boca, o Mutirão de Prevenção ao Câncer é de suma importância, uma vez que permite o rastreamento, o diagnóstico precoce e um melhor prognóstico.